Дослідження каталітичної активності Мо2В в реакції β-етилаліл-α-етилакрилату з трет-бутилгідропероксидом - Комаренська, З. М.; Макота, О. І.; Олійник, Л. П.; Яковенко, Ю.; Komarenska, Z. M.; Makota, O. I.; Oliynyk, L. P.; Yakovenko, Yu. (Lviv Politechnic Publishing House, 2023)
Досліджено кінетичні закономірності процесів активації каталізатора в реакції епоксидування етилалілетилакрилату гідропероксидом трет-бутилу у присутності Мо2В. Показано, що активація каталізатора на початку процесу епоксидування переважно відбувається за одночасної дії на нього гідропероксиду трет-бутилу й олефіну. Здатність до комплексоутворення з реагентами і продуктами реакції в неактивованого каталізатора значно нижча, ніж в активованого, й епоксид утворюється фактично тільки на активованій формі каталізатора. Показано, що процес активування каталізатора описується топохімічним рівнянням Аврамі – Єрофеєва і містить дві послідовні стадії – зародкоутворення і формування нової активної в реакції епоксидування фази.

Kinetic regularities of catalyst activation processes in the reaction of epoxidation of ethylallyl ethyl acrylate with tert-butyl hydroperoxide in the presence of Mo2B were investigated. It is shown that the activation of the catalyst, which takes place at the beginning of the epoxidation process, mainly occurs under the simultaneous action of tert-butyl hydroperoxide and olefin. The ability to create complex with reactants and reaction products for the unactivated catalyst is significantly lower than for the activated one, and the formation of epoxide occurs practically only on the activated form of the catalyst. It is shown that the catalyst activation process can be described by the Avrami-Yerofeev topochemical equation and includes two successive stages - nucleation and formation of a new phase active in the epoxidation reaction.
Study of the catalytic activity of Mo2B in the reaction of β-ethyl allyl-α-ethyl acrylate with tert-butyl hydroperoxide
Keywords: окиснення; епоксидування; кінетичні закономірності; каталізатор; β-етилаліл-α-етилакрилат; oxidation; epoxidation; kinetic patterns; catalyst; β-ethylallyl-α-ethyl acrylate